Efeito do treino de palavras com controle temático e formal na aquisição de resposta intraverbal - Larissa dos Santos Costa (2024)
Skinner described verbal behavior as operant behavior in which the consequence is mediated by a trained listener within the verbal community; responses can vary in function and form based on antecedent-consequent relations. This includes Thematic and Formal Control, though in intraverbal behavior, both controls may overlap. This study aimed to observe the effects on Intraverbal verbal repertoire after training with words under formal and thematic control. Ten volunteers from the Federal University of Mato Grosso do Sul participated. Training involved 12 pairs of invented words, divided into thematic and partially formal control blocks, and thematic-only blocks, with echoic training preceding intraverbal. Participant responses to pair correspondences were recorded, investigating thematic and formal relations. Results, encompassing total participant responses, showed slightly higher performance for rhyming words. However, study limitations, like the small sample size, must be considered for broader interpretation.